2017
DOI: 10.1111/1744-9987.12557
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Efficacy of Double‐Filtration Plasmapheresis in Treating Five Patients With Drug‐Resistant Pemphigus

Abstract: Double-filtration plasmapheresis is an effective and safe treatment for pemphigus. We retrospectively evaluated the decrease in autoantibody titer and pemphigus disease area index following double-filtration plasmapheresis in five patients with moderate to severe pemphigus, who were physically and/or serologically unresponsive to 1.0 mg/kg per day of prednisolone and other supportive drugs and ointments. The percentage reduction in autoantibodies 85.6 ± 14.4% (P = 0.00014), and that in pemphigus disease area i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Double filtration plasmapheresis (DFPP) is a relatively new procedure that, similar to IA, removes selectively immunoglobulins, while minimizing the loss of albumin. In small case series and one retrospective study DFPP also demonstrated efficacy in drug resistant pemphigus (230232).…”
Section: Treatmentmentioning
confidence: 98%
“…Double filtration plasmapheresis (DFPP) is a relatively new procedure that, similar to IA, removes selectively immunoglobulins, while minimizing the loss of albumin. In small case series and one retrospective study DFPP also demonstrated efficacy in drug resistant pemphigus (230232).…”
Section: Treatmentmentioning
confidence: 98%
“…Nevertheless, there are other alternative methods of plasmapheresis, such as double filtration plasmapheresis (DFPP). DFPP is a semi‐selective method in which the patient's blood passes through a first filter (plasma separator), dissociating the formed elements of the blood and the plasma, which is then filtered by a second filter (plasma fractionator) permitting the extraction of the substance of interest according to its size 7 …”
mentioning
confidence: 99%
“…Though several case reports or series also reported the capability of plasmapheresis in inducing remission in severe or refractory pemphigus patients, 19,20,22,[30][31][32] high quality evidence was still lacking. In the American Society for Apheresis guidelines updated in 2019, plasmapheresis was recommended as category III (optimum role of apheresis therapy is not established), Grade 2B (weak recommendation, low-quality or very low-quality evidence) with the indication of severe cases.…”
Section: Discussionmentioning
confidence: 99%
“…17 Since then, there have been quite a few researches in this field, but the results are controversial. [18][19][20] The utilized techniques of plasmapheresis are also different in these studies. 21,22 Double filtration plasmapheresis (DFPP) is superior to other techniques, because it can increase the selectivity of the molecular size.…”
Section: Introductionmentioning
confidence: 99%